CRITIQUE OF THE SUBORDINATION OF RELIGION BY THE JAVANESE STATE IN HIKAYAT MARESKALEK: KRITIK TERHADAP SUBORDINASI AGAMA OLEH NEGARA JAWA DALAM HIKAYAT MARESKALEK - Riqko Nur Ardi Windayanto, (Jurnal Pengajian Melayu (JOMAS), 2025)
ABSTRACT This study discusses the critique of the subordination of the state’s subordination of religion in Abdullah bin Muhammad al-Misri’s Hikayat Mareskalek, revealed through the interpretation of the episode depicting the encounter between Mareskalek and Susuhunan Kalijaga. This topic is examined due to its relevance to the relationship between the state and religion, offering insights into the author’s ideas underlying the critique. The study addresses two main issues: the meaning of the encounter between the two characters and the implications of the critique embedded in it. This study aims to generate knowledge about the state-religion relationship as a critical reflection on the role of religion in the formation of the nation-state. Methodologically, this study applies Mieke Bal’s narratology theory (particularly the concept of actor opposition) and hermeneutic interpretation to address the first issue, while dialectical analysis is used to examine the critical context pertaining to the second issue. This study shows that the encounter between the two characters builds an oppositional relationship that symbolically critiques the Javanese state (the Mataram–Surakarta Sultanate), which subordinated Islam to political power by transforming the title susuhunan from a spiritual saint (wali) to a royal title. al-Misri emphasizes the importance of state and the religion being equal in status, and the role of religious scholars (ulama) as a central consultive authority, based on Wahhabi thought in the 19th century. Based on these findings, it can be concluded that Hikayat Mareskalek is not merely a work of fiction, but a piece that offers political ideas as a critical reflection relevant to contemporary debates on the relationship between the state and religion. Keywords: religion-state; Hikayat Mareskalek; Java; Malay literature; subordination ABSTRAK Kajian ini membincangkan kritikan terhadap subordinasi agama oleh negara dalam Hikayat Mareskalek karya Abdullah bin Muhammad al-Misri yang diungkap melalui penafsiran episod pertemuan antara Mareskalek dan Susuhunan Kalijaga. Topik ini dikaji kerana berkaitan dengan hubungan antara negara dan agama, serta memperlihatkan gagasan pengarang yang mendasari kritikan tersebut. Berdasarkan pertimbangan itu, kajian ini menjawab dua persoalan utama, iaitu makna pertemuan kedua-dua tokoh dan implikasi kritikan yang terkandung di dalamnya. Tujuan kajian ini ialah untuk menghasilkan pengetahuan baru tentang hubungan antara negara dan agama sebagai refleksi kritikal dalam menilai peranan agama dalam pembentukan negara-bangsa. Dari segi metodologi, kajian ini menggunakan teori naratologi, khususnya konsep oposisi watak oleh Mieke Bal, serta tafsiran hermeneutik untuk menjawab persoalan pertama, manakala analisis dialektik digunakan untuk meneliti konteks kritikan bagi menjawab persoalan kedua. Hasil kajian menunjukkan bahawa pertemuan kedua-dua tokoh membentuk hubungan oposisi yang secara simbolik mengkritik negara Jawa (Kesultanan Mataram—Surakarta) yang telah menundukkan Islam demi kepentingan kekuasaan melalui transformasi gelaran susuhunan daripada gelaran wali menjadi gelaran raja. Al-Misri menekankan kepentingan agar negara dan agama berada pada kedudukan yang setara serta peranan ulama sebagai pihak berautoriti dalam konsultasi politik, berasaskan pemikiran Wahabi abad ke-19. Berdasarkan penemuan ini, dapat disimpulkan bahawa Hikayat Mareskalek bukan sekadar karya fiksyen, tetapi sebuah buku teks yang menawarkan gagasan politik sebagai refleksi kritikal yang relevan dengan perbahasan kontemporari mengenai hubungan antara negara dan agama. Kata kunci: agama-negara; Hikayat Mareskalek; Jawa; kesusasteraan Melayu; subordinasi